1997
DOI: 10.1097/00002030-199714000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous methotrexate for primary central nervous system non-Hodgkinʼs lymphoma in AIDS

Abstract: Methotrexate appears to be an attractive alternative to radiation therapy for primary CNS lymphoma and is associated with a far greater improvement in quality of life relative to historical series of radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(42 citation statements)
references
References 16 publications
0
40
0
2
Order By: Relevance
“…Survival may be improved in the HAART era, with patients responding to HAART treatment demonstrating extended median survivals to beyond 1.5 years [126]. Smaller reports in this population have also shown responses to high-dose methotrexate-based regimens without the associated leukoencephalopathy of whole-brain radiation [127]. Pilot studies have also suggested promise for therapy directed against EBV and HIV in the form of parenteral zidovudine, ganciclovir, and IL-2 along with HAART [128], although these results are still preliminary.…”
Section: Treatmentmentioning
confidence: 99%
“…Survival may be improved in the HAART era, with patients responding to HAART treatment demonstrating extended median survivals to beyond 1.5 years [126]. Smaller reports in this population have also shown responses to high-dose methotrexate-based regimens without the associated leukoencephalopathy of whole-brain radiation [127]. Pilot studies have also suggested promise for therapy directed against EBV and HIV in the form of parenteral zidovudine, ganciclovir, and IL-2 along with HAART [128], although these results are still preliminary.…”
Section: Treatmentmentioning
confidence: 99%
“…This approach resulted in a 50% complete response rate and a median survival of 10 months. 92 With the use of HAART, PCNSL therapy appears to have become more tolerable and as in non-HIV PCNSL, there has been more interest in using systemic chemotherapy with or without radiotherapy to improve quality of life and minimize long-term sequelae of radiotherapy alone. More recent cohort data suggest that immune recovery associated with HAART can dramatically improve survival.…”
Section: Primary Cns Lymphomamentioning
confidence: 99%
“…The concept of using high-dose MTX in PEL initially came from the observation of a patient with a secondary localization of PEL in the central nervous system (CNS) (case 1). As MTX has been successfully used in the treatment of AIDS-associated primary CNS lymphoma [8], this drug was added to the chemotherapy regimen. The achievement of a sustained complete remission (CR) in this patient as well as the potential for MTX to diffuse in the body cavities and to accumulate in serous effusions prompted us to use it in the chemotherapy given for PEL.…”
Section: Introductionmentioning
confidence: 99%